Perempuan, Digitalisasi, dan Kebebasan Berekspresi: Kajian Hukum Tentang Perlindungan Hak Asasi di Ruang Siber - Siti Fatimah; Aisyah Rukmi Widowati; Azahery Insan Kamil (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
Digitalization has significantly transformed various aspects of life, including expanding women’s freedom of expression in cyberspace. However, it also brings challenges such as online gender-based violence (OGBV), cyber harassment, and violations of women’s human rights. This article analyzes the intersection of women, digitalization, and freedom of expression from a legal perspective, focusing on national and international legal protections. The discussion includes women’s human rights in the digital age, the balance between freedom and legal limitations, and the impact of digitalization on these rights. It also examines regulatory frameworks related to freedom of expression and the challenges women face in cyberspace, particularly regarding OGBV and the effectiveness of law enforcement. Through case analysis, this study evaluates whether current laws adequately protect women online. The article proposes policy reform, emphasizing the roles of government, digital platforms, and civil society in fostering a safer, more inclusive digital space. Key recommendations include revising the Electronic Information and Transactions Law and strengthening the Sexual Violence Crime Law. A collaborative, multidisciplinary approach is essential to uphold women’s freedom of expression while ensuring their safety and rights in the digital era.